1991
DOI: 10.1111/j.0022-3646.1991.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF SETTLEMENT DENSITY ON GAMETOPHYTE GROWTH AND REPRODUCTION IN THE KELPS PTERYGOPHORA CALIFORNICA AND MACROCYSTIS PYRIFERA (PHAEOPHYCEAE)1

Abstract: Laboratory studies were used to examine how variation in the density of spore settlement influences gametophyte growth, reproduction, and subsequent sporophyte production in the kelps Pterygophora californica Ruprecht and Macrocystis pyrifera (L.) C. Ag. In still (non‐aerated) cultures, egg maturation in both species was delayed when spores were seeded at densities 300 · mm−2. Although the density at which this inhibition was first observed was similar for both species, the age at which their eggs matured was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 23 publications
7
97
2
Order By: Relevance
“…However, in this experiment, no significant mean plant weight-density relationship was found, whereas the density-standing crop relationship was strong, so the measure seemed to be a valid one. We found no significant evidence of density dependent mortality in our laboratory populations of Fucus vesiculo.su.s, a response which has been found in other young fucoids (Ang & De Wreede 1992) and kelps (Black 1974, Reed 1990a, Reed et al 1991. Probably, the earliest signs of negative density dependence are reduced growth rates, and only at a later stage does mortality start to take a toll.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…However, in this experiment, no significant mean plant weight-density relationship was found, whereas the density-standing crop relationship was strong, so the measure seemed to be a valid one. We found no significant evidence of density dependent mortality in our laboratory populations of Fucus vesiculo.su.s, a response which has been found in other young fucoids (Ang & De Wreede 1992) and kelps (Black 1974, Reed 1990a, Reed et al 1991. Probably, the earliest signs of negative density dependence are reduced growth rates, and only at a later stage does mortality start to take a toll.…”
Section: Discussioncontrasting
confidence: 59%
“…specific seaweed populations. For ~nstance Reed et al (1991) found that kelp spores needed a minimum density for subsequent fertilization and sporophyte pro-MATERIALS AND METHODS duction. 'Safety-in-numbers' factors may be responsible for other reports of higher survival at higher Laboratory populations.…”
Section: Introductionmentioning
confidence: 99%
“…In species such as the kelps that have a microscopic life history phase, intense intraspecific competition almost certainly can occur. In a series of field (Reed, 1990) and laboratory (Reed, Neushul & Ebeling, 1991) experiments, a minimum settlement density of at least 1 zoospore mm 2 was needed for successful sporophyte recruitment in Macrocystis pyrifera and Pterogophora californica (presumably to insure successful fertilization). Above this critical density, however, strong density-dependent mortality occurred whenever there was sporophyte recruitment.…”
Section: Microclimates Of the Benthosmentioning
confidence: 99%
“…Consequently, Pterygophora gemetophytes mature at a faster rate than do Macrocystis gametophytes (Reed, Neushul & Ebeling, 1991 (Silvertown, 1982). Over-exploitation of a shared resource may not have been the sole mechanism of competition between the two kelps since inhibition of Macrocystis by Pterygophora was observed at low as well as high densities of spore settlement (Reed, 1990).…”
Section: Microclimates Of the Benthosmentioning
confidence: 99%
“…In addition, it has been shown to help retain moisture and reduce heat stress during low tides among organisms living in the group (Scrosati & DeWreede, 1998). In the particular case of kelps, Reed et al (1991) showed that a minimum spore density was necessary for sporophyte production in Pterygophora californica and Macrocystis pyrifera, and more recently, Muth (2012) demonstrated that sporophyte production significantly increased as spores became more aggregated in the species M. pyrifera. However, our study was not designed to discriminate between these two hypotheses; thus, it would be interesting to carry out a separate study to specifically address spore settlement.…”
Section: Laminaria Digitatamentioning
confidence: 99%